THE USE OF INSTAGRAM BY FASHION BRANDS IN DIGITAL MARKETING - Islam, Ifrah; Pavlíček, Antonín, 1977-; Potančok, Martin; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
One of the greatest economic engines in the world, the fashion industry, has found an effective online communication strategy. In order to adapt and reach expanding markets ready to buy fashion, fashion brands reinvent themselves with regards to their operations and advertising strategies. For this reason, digital marketing has become a vital instrument for reaching the younger audiences of these industry leaders. Because the fashion business is dynamic and ever-evolving, brands are starting to look for influencers to help them spread messages about their products or brands in order to boost online visibility, project a particular image, or elevate their status. For this reason, businesses are concentrating on social media marketing, and 84% of businesses say they have included social media into their conventional marketing initiatives. In the current era of social media, with millions of daily users. Instagram has overtaken numerous rival applications to emerge as the most widely utilized social networking app, where individuals can convey oneself by uploading content to their accounts and building a variety of creative content. It has caught the attention of marketers, and over half of the biggest brands worldwide are currently making use of this platform. for marketing and audience engagement, but various brands use different approaches to reach their target demographic. Because of their unique approaches and uses of Instagram, every brand on the platform has a varied performance. To examine these variations, the present research aims to understand the strategies employed by these renowned brands and to compare and contrast the strategies utilized by these brands. Moreover, to uncover patterns and successful approaches in their Instagram marketing efforts.
Vedoucí práce: Antonín Pavlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses